Tero Buro: Feature film script - Miami, Silas (Centre for Film and Media Studies, 2021)
The conflict and controversy sparked by the production and public consumption of creative work wherein African queerness is liberally expressed is rarely explored from the perspective of the African queer creative. This paper examines how South African queer creatives interpret and understand the often-tumultuous reception that exhibitions of queerness in film and television receive from largely heterosexual South African audiences. With its focus trained on locating the labor concomitant to queer visibility, labor carried predominantly by members of the queer community, it interrogates the positioning of cinematic presentations of African queerness within South Africa's past and current social and cultural landscape by examining how performative resistance of African queer narratives impact the Black queer creative community in South Africa. Finally, this study critically explores the line of reasoning behind the displacement central to arguments that simultaneously seek to strip African queerness of any legitimate claim to ownership of indigenous African cultures and stories. Jon Trengrove's film, Inxeba (The Wound) (2017), functions as this paper's primary text. Inxeba's conceptualisation, production, reception, and the controversy that succeeded its release will ultimately ground this paper's examination of the consequential impact that its exhibition's spectacle had on the lives, and production outputs, of Black African queer creatives